2018
DOI: 10.1002/cctc.201801350
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Electron Distribution and Synergetic to Enhance Catalytic Activity in Bimetallic Ni(II)/Pd(II) Molecular Monolayer

Abstract: Novel graphene oxide (GO)‐supported ordered diimine Ni/Pd bimetallic monolayers with ratio of Ni to Pd atomic ratios (2136 : 1, 333 : 1 and 97 : 1) (denoted as GO‐Diimine‐Ni/Pd1, GO‐Diimine‐Ni/Pd2, GO‐Diimine‐Ni/Pd3) were fabricated and their catalytic performances and synergetic mechanism were systematic investigated. For the as‐prepared GO‐Diimine‐Ni/Pd1, that trace palladium complex was responded for changing the electronic environment, tuning catalytic actives and modifying the electronic states which coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 72 publications
1
33
0
Order By: Relevance
“…[25,26] The presence of a high density of carbonyl, hydroxyl and carboxylic acid groups on the biochar surface allows the modification of its surface via reaction with dopamine, alkoxysilane and other reagents which can be used as a support for the immobilization of catalysts or other substances. [33][34][35][36][37][38][39][40] The use of palladium-phosphine catalysts involves expensive, toxic and air-and moisture-sensitive procedures. Biochar is a stable solid in air atmosphere, at high temperature and in aqueous solution, and therefore biochar is an ideal catalyst support for organic processes occurring under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] The presence of a high density of carbonyl, hydroxyl and carboxylic acid groups on the biochar surface allows the modification of its surface via reaction with dopamine, alkoxysilane and other reagents which can be used as a support for the immobilization of catalysts or other substances. [33][34][35][36][37][38][39][40] The use of palladium-phosphine catalysts involves expensive, toxic and air-and moisture-sensitive procedures. Biochar is a stable solid in air atmosphere, at high temperature and in aqueous solution, and therefore biochar is an ideal catalyst support for organic processes occurring under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1 For hetero-bimetallic catalysts, an investigation on the relationship between their activity and structure is deeply studied for understanding the synergism between the different components. [2][3][4] Recently, the synergistic catalysis with trimetallic catalysts have received considerable interest, 5 and the real active centers remain unknown because each component is responsible for different steps in the overall transformation. 6 Meanwhile, there has been rapidly growing interest in multi-component catalysts, in which improving the activity and reducing expenses are considered to be key issues for heterogeneous catalyst, 7,8 and are particularly important for noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…15 Therefore, substituting palladium with less expensive doped transition metals is expected for achieving higher activity and reducing the catalyst costs. For example, some economic transition metals include nickel with its charge-donating ability, 4,9 and the charge transferring and stabilizing property of Fe. 8,16 Ruthenium is one of the cheapest precious metals having broad application prospects, 17,18 and has long been considered as one of the effective components in a catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Previous studies have shown that the catalytic activity of the heterobimetallic catalysts could be enhanced by tuning their composition, morphology and the relative distributions of electrons, which are related to the electrical characteristics of the ligand, supports, and the synergy of hetero-bimetals. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Appropriate supports could promise a high dispersion of metallic catalyst and the maximum utilization of noble materials has attracted much attention; 19,40 graphene oxide (GO) has been recognized as an ideal candidate for supporting various metals and their complexes. [41][42][43] Pd catalyst doped with Ni, Fe, Co or Cu, reduces the loading of Pd and signicantly enhances catalytic activity by adjusting the distance between nickel and palladium, charge distribution and the arrangement of active sites.…”
Section: Introductionmentioning
confidence: 99%